The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.1177/0960327112462727
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diindolylmethane on Ca2+ homeostasis and viability in MDCK renal tubular cells

Abstract: The effect of the natural product diindolylmethane (DIM) on cytosolic Ca(2+) concentrations ([Ca(2+)]i) and viability in MDCK renal tubular cells was explored. The Ca(2+)-sensitive fluorescent dye fura-2 was applied to measure [Ca(2+)]i. DIM at concentrations 1-50 μM induced a [Ca(2+)]i rise in a concentration-dependent manner. The response was reduced partly by removing Ca(2+). DIM induced Mn(2+) influx leading to quenching of fura-2 fluorescence. DIM-evoked Ca(2+) entry was suppressed by nifedipine, econazol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The [Ca 2+ ] i was measured as previously described (6,8,11,23,32). Confluent cells grown on 6 cm dishes were trypsinized and suspended in culture medium at a density of 10 6 /ml.…”
Section: [Ca 2+ ] I Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…The [Ca 2+ ] i was measured as previously described (6,8,11,23,32). Confluent cells grown on 6 cm dishes were trypsinized and suspended in culture medium at a density of 10 6 /ml.…”
Section: [Ca 2+ ] I Measurementsmentioning
confidence: 99%
“…Viability was assessed as previously described (6,8,11). The measurement of viability was based on the ability of cells to cleave tetrazolium salts by dehydrogenases.…”
Section: Cell Viability Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of extracellular Ca 2+ , the addition of the ER Ca 2+ pump inhibitor 2,5‐di‐ tert ‐butylhydroquinone, and suppression of phospholipase C abolished DIM‐induced cytosolic Ca 2+ rise. DIM has been reported to induce Ca 2+ release from the ER of human hepatoma, prostate, and renal tubular cancer cell . Staining with Annexin V/propidium iodide showed that DIM induced apoptosis in a concentration‐dependent manner.…”
Section: Introductionmentioning
confidence: 99%